PELATIHAN MEDIA PEMBELAJARAN BERBASIS MEDIA ONLINE MENGGUNAKAN GOOGLE CLASSROOM DAN GOOGLE FORM DI DESA PENINJAUAN KABUPATEN OGAN KOMERING ULU - M. Rudi Sanjaya; Endang Lestari Ruskan; Dwi Rosa Indah; Ariansyah Saputra; Rafliandi Ardana; Muhammad Raihan Udda Rahmany; Novitas Sari; Rahma Destriani (Aptekmas Jurnal Pengabdian pada Masyarakat, 2021)
In this 4.0 industrial revolution, teachers are currently guided to have skills in the field of technology in making online learning media, especially the Miftahul Jannah Islamic Boarding School in the observation village. In the survey village, they did not know how to make online-based learning media, namely google classroom and google form. The purpose of this community service activity is to increase the knowledge and skills of teachers at the Sanawiyah and Aliyah levels in making google classroom-based learning media so that it can improve the learning outcomes of santri at the Miftahul Jannah Village Islamic boarding school by using online media. The benefits of this training activity are: Increase understanding of the creation of learning media, especially Google Classroom and Google Forms, Can or can create Google and Google Classroom and Google Forms accounts and can create classes in Googlee Classroom and Google Forms so that they can be applied and implemented in the learning process teaching, the method of implementing this training is to provide and explain material, question and answer, discussion and practice of making online-based learning media